2019
DOI: 10.1001/jamainternmed.2019.1201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Self-management Support Intervention on Asthma Outcomes in Older Adults

Abstract: IMPORTANCE Older adults with asthma have worse control and outcomes than younger adults. Interventions to address suboptimal self-management among older adults with asthma are typically not tailored to the specific needs of the patient. OBJECTIVE To test the effect of a comprehensive, patient-tailored asthma self-management support intervention for older adults on clinical and self-management outcomes. DESIGN, SETTING, AND PARTICIPANTS Three-arm randomized clinical trial conducted between February 2014 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 42 publications
1
35
0
1
Order By: Relevance
“…The common barriers to medication adherence for CVD include unaffordable costs, lack of belief in the necessity of medication, side effects of medication or medication concerns, complex regimens, forgetfulness, lack of family or social support, depression, lack of disease knowledge, and inconvenient access to medications or care ( Choudhry et al, 2011 ; Nair et al, 2011 ; Müller et al, 2015 ; Zullig et al, 2015 ; Banerjee et al, 2016 ; Crawshaw et al, 2016 ; Xavier et al, 2016 ; Wang et al, 2019 ). There are some uncommon barriers that are reported relatively less often such as asymptomatic diseases ( Devine et al, 2018 ), a poor provider–patient relationship, lack of understanding of the benefits of medication, prioritization issues or a busy lifestyle, disruptions to daily routines, and stigma or social embarrassment ( Quach et al, 2009 ; Gellad et al, 2011 ; Nair et al, 2011 ; Farsaei et al, 2014 ; Müller et al, 2015 ; Newman-Casey et al, 2015 ; Zullig et al, 2015 ; Campbell et al, 2016 ; Sweileh, 2018 ; Venditti et al, 2018 ; Federman et al, 2019 ; Sweileh et al, 2019 ). For CVD, there are several diseases or conditions that may be symptomless such as hypertension, hypercholesterolemia, and even coronary heart diseases in some cases.…”
Section: Present State Of Tailored Interventions For Medication Adhermentioning
confidence: 99%
“…The common barriers to medication adherence for CVD include unaffordable costs, lack of belief in the necessity of medication, side effects of medication or medication concerns, complex regimens, forgetfulness, lack of family or social support, depression, lack of disease knowledge, and inconvenient access to medications or care ( Choudhry et al, 2011 ; Nair et al, 2011 ; Müller et al, 2015 ; Zullig et al, 2015 ; Banerjee et al, 2016 ; Crawshaw et al, 2016 ; Xavier et al, 2016 ; Wang et al, 2019 ). There are some uncommon barriers that are reported relatively less often such as asymptomatic diseases ( Devine et al, 2018 ), a poor provider–patient relationship, lack of understanding of the benefits of medication, prioritization issues or a busy lifestyle, disruptions to daily routines, and stigma or social embarrassment ( Quach et al, 2009 ; Gellad et al, 2011 ; Nair et al, 2011 ; Farsaei et al, 2014 ; Müller et al, 2015 ; Newman-Casey et al, 2015 ; Zullig et al, 2015 ; Campbell et al, 2016 ; Sweileh, 2018 ; Venditti et al, 2018 ; Federman et al, 2019 ; Sweileh et al, 2019 ). For CVD, there are several diseases or conditions that may be symptomless such as hypertension, hypercholesterolemia, and even coronary heart diseases in some cases.…”
Section: Present State Of Tailored Interventions For Medication Adhermentioning
confidence: 99%
“…Of note, other trials in older adults that have found that decreased exacerbation rates do not always show meaningful changes in lung function parameters. 13,14 The intervention was specifically designed to have individual components as well as group interaction. Group sessions have been found to be effective for older adults in a number of interventions and conditions, such as diabetes and osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Trained lay health workers (also known as community health workers) can deliver discrete areas of respiratory care such as asthma self-management education. In one study, this was associated with increased symptom-free days and reduced healthcare utilization compared with usual care, 397 in another study, with improved adherence, inhaler technique, symptom control and quality of life and reduced emergency department visits compared with usual care, 371 and in a third study, comparable outcomes to those achieved by practice nurses based in primary care 398 (Evidence B). These findings suggest the need for additional studies to assess applicability in other settings and populations.…”
Section: Asthma Informationmentioning
confidence: 98%
“…Pharmacists, nurses and trained lay health workers can provide highly effective inhaler skills training. 362,[369][370][371] Some inhaler devices and techniques for their use are illustrated on the GINA website (www.ginasthma.org) and the ADMIT website (www.inhalers4u.org). • If different options are available, encourage the patient to participate in the choice…”
Section: Skills Training For Effective Use Of Inhaler Devicesmentioning
confidence: 99%